The Orenburg Political Link as the Mechanism of Accumulation: the Case of Bronislav Zalesky and Candid Zelenko - Lyubichankovskiy, Sergey (Przegląd Wschodnioeuropejski, 2018)
The article is devoted to the analysis of life and activities in the Orenburg region of Bronislaw Zalessky and Kandid Zelenko, who were exiled there for political reasons in the first half of the XIX century. The theoretical basis of the article is the concept of acculturation. The study is based primarily on unpublished sources from the State Archives of the Orenburg region, with respect to which the method of historical reconstruction has been used. It is concluded that people who were exiled to a remote province eventually became embedded in the structure of the local society in such a way that they became the vehicles of European culture and education in the Orenburg region. At the same time, they themselves in the course of living in exile fell in love with the place of their exile, became its patriots and popularizers outside the borders of the Russian Empire.